A weak Kalman decomposition approach for reduced realizations of switched linear systems. Issue 20 (2022) - Hossain, Md Sumon; Trenn, Stephan
Abstract: We propose a novel reduction approach for switched linear systems with a fixed mode sequence based on subspaces related to the (time-varying) reachable and unobservable spaces. These subspaces are defined in such a way that they can be used to construct a weak Kalman decomposition, which is then in turn used to define a reduced switched linear system with an identical input-output behavior. The proposed method is illustrated with a low dimensional academic example.